CRIMINAL-LEGAL ANALYSIS OF THE SPECIAL SUBJECT OF CRIMES WITH ATTRIBUTES OF A PUBLIC OFFICIAL - Kumrinisa , Abdurasulova (International Journal of Business, Law and Political Science, 2024)
The article is devoted to the criminal-legal analysis of a special subject of a crime having the attributes of a public official. An official is a special subject and the offences committed by him are directly related to his official position. A person may use official information as well as other means to achieve his goal, based on his official duties. Although official offences do not have a large share in the overall structure of crime, they pose a great danger to society, the state and citizens. o date, the issues related to the prosecution of a person who has committed an official offence remain controversial.